NESTED LIVES”- UNVEILING THE MYSTERIES OF CELL IN CELL PHENOMENON (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Cell in cell structure refers to a phenomenon in which one viable or dying cell is completely enclosed within another living cell.  Cell in cell structures are most commonly described in tumors particularly melanoma, aggressive carcinomas, immune interactions and developmental processes. They arise through mechanism such as entosis, emperipolesis and cell cannabalism, each involving distinct cellular and molecular pathways. Aims & Objectives: To study the different cell in cell phenomenon in various disease process, it’s mechanism and the pathological significance of cell in cell structures. Materials and Methods: This is retrospective study of 22 cases of cell in cell structures is studied 3 years from April 2023 to March 2026. Results:Our study shows female predominance with ratio of 1.2:1(F:M).Among 22 cases nine cases (40.91%) were found in 41 to 50 years of age. Out of 22 cases 12 (54.5%) cases were malignant and 10 (45.5%) benign cases were noted. Out of 22 cases 9 (40.91%) were cell cannibalism, 7 (31.82%) were phagocytosis, 6 (27.27%) were emperipolesis. Discussion and Conclusion:  Cell in cell structures should be identified during routine reporting in both benign and malignant diseases, as advances in microscopy and molecular profiling of these fascinating phenomenon provide insights to their diagnostic, prognostic and therapeutic importance.